Dispositional traits, motivation, and perfomance strategies of South African National Defence Force soldiers : developing a descriptive psychological perfomance model - Cassimjee, Nafisa (University of Pretoria, 2023)
Thesis (PhD (Psychology))--University of Pretoria, 2022.